Hard and Soft Smart Cities: An Integrated Approach - Senatore, Gianluca; Sessa, Melissa (SocietàMutamentoPolitica, 2023)
This contribution aims to critically analyse smart city processes. The distinction between soft and hard smart cities goes in this direction. On the one hand, the smart city appears to be the result of a sustainable transition; on the other, it seems to live only thanks to technologies. This dichotomy, as will be seen, leaves out a whole series of social processes that also make up the smart city. Where then is the social dimension within this reasoning? The social dimension seems to be rediscovered not so much and not only in the interaction between all the actors of smartness, but also and above all in the complex interpretation offered by smartness, which does not seem to be referable only to technology and sustainability.